Fabrication of AgCl/Ag3PO4/graphitic carbon nitride heterojunctions for enhanced visible light photocatalytic decomposition of methylene blue, methylparaben and E. coli. Issue 11 (4th February 2021) - Li, Haishuai; Cai, Linlin; Wang, Xin; Shi, Huixian
Abstract : A noval ternary nanocomposite AgCl/Ag3 PO4 /g-C3 N4 was successfully synthesized for photocatalytic degradation of methylene blue, methylparaben and inactivation of E. coli under visible light irradiation, showing excellent photocatalytic degradation performance and stability. Abstract : Herein, a novel ternary nanocomposite AgCl/Ag3 PO4 /g-C3 N4 was successfully synthesized via sedimentation precipitation and ion exchange method. The photocatalytic performance of the as-prepared AgCl/Ag3 PO4 /g-C3 N4 nanocomposite was investigated via photocatalytic degradation of methylene blue (MB), methylparaben (MPB) and inactivation of E. coli under visible light irradiation. The AgCl/Ag3 PO4 /g-C3 N4 composite presented the optimal photocatalytic performance, degrading almost 100% MB and 100% MPB, respectively. The excellent stability of AgCl/Ag3 PO4 /g-C3 N4 was also verified in the cycle operations; the degradation efficiency of MPB could still be maintained at 85.3% after five cycles of experiments. Moreover, the AgCl/Ag3 PO4 /g-C3 N4 composite displayed more superior photocatalytic inactivation efficiency with 100% removal of E. coli (7-log) in 20 min under visible light irradiation. The efficient photo-generated charge separation originated from a strong interaction in the intimate contact interface, which was confirmed by the results of photocurrent and EIS measurements. In addition, radical trapping experiments revealed that hole (h + ) was the predominant active species in the photocatalytic system. Based on the experimental results, a photocatalytic mechanism for the degradation of parabens over AgCl/Ag3 PO4 /g-C3 N4 was also proposed. We believe that this work provides new insights into the multifunctional composite materials for the applications in solar photocatalytic degradation of harmful organic compounds and common pathogenic bacteria in wastewater.